The impact of fatigue on patients with psoriatic arthritis: a multi-center study of the TLAR-network - GEZER, HALİSE HANDE; DURUÖZ, MEHMET TUNCAY; ACER KASMAN, SEVTAP (SPRINGER HEIDELBERG, 2020)
Fatigue is a substantial problem in patients with psoriatic arthritis (PsA) that needs to be considered in the core set of domains. This study aimed to evaluate fatigue and its relationship with disease parameters, functional disability, anxiety, depression, quality of life, and correlation with disease activity as determined by various scales. A total of 1028 patients (677 females, 351 males) with PsA who met the CASPAR criteria were included [Turkish League Against Rheumatism (TLAR) Network multicenter study]. The demographic features and clinical conditions of the patients were recorded. Correlations between fatigue score and clinical parameters were evaluated using the Disease Activity Score 28 (DAS28), Disease Activity in Psoriatic Arthritis (DAPSA), Clinical DAPSA (cDAPSA), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), the Fibromyalgia Rapid Screening Tool (FiRST), minimal disease activity (MDA), and very low disease activity (VLDA). Fatigue was assessed with the Functional Assessment of Chronic Illness Therapy (FACIT-F) and a 10-point VAS (VAS-F). The mean age of the patients was 47 (SD: 12.2) years, and the mean disease duration was 6.4 (SD: 7.3) years. The mean VAS-F score was 5.1 (SD: 2.7), with fatigue being absent or mild, moderate, and severe in 12.8%, 24.6%, and 62.5% of the patients, respectively. Fatigue scores were significantly better in patients with DAS28 remission, DAPSA remission, cDAPSA remission, MDA, and VLDA (p < 0.001). Fatigue scores significantly increased with increasing disease activity levels on the DAS28, DAPSA, and cDAPSA (p < 0.001). VAS-F scores showed correlations with the scores of the BASDAI, BASFI, PsAQoL, HAD-A, FiRST, pain VAS, and PtGA. FiRST scores showed fibromyalgia in 255 (24.8%) patients. FACIT-F and VAS-F scores were significantly higher in patients with fibromyalgia (p < 0.001). In regression analysis, VLDA, BASDAI score, FiRST score, high education level, HAD-Anxiety, and BMI showed independent associations with fatigue. Our findings showed that fatigue was a common symptom in PsA and disease activity was the most substantial predictor, with fatigue being less in patients in remission, MDA, and VLDA. Other correlates of fatigue were female gender, educational level, anxiety, quality of life, function, pain, and fibromyalgia.
Keywords: Psoriatic arthritis; Fatigue; Lassitude; Disease activity; Outcome measure; BATH ANKYLOSING-SPONDYLITIS; RHEUMATOID-ARTHRITIS; DISEASE-ACTIVITY; OUTCOME MEASURE; INDEXES; RELIABILITY; PREVALENCE; DEPRESSION; ANXIETY; SYMPTOM